2021
DOI: 10.3389/fpubh.2021.772933
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks in Limbo. The Experiences of Older Adults During COVID-19 in Ghana

Abstract: While studies exploring COVID-19 and its global influence have begun, social networks and support among older adults in low-and middle-income countries, such as Ghana have been inadequate despite its enormous relevance. Thus, the study presents the voices of older adults in Jamestown, Accra and their social networks during the COVID-19 pandemic in Ghana. Using a phenomenological approach, data were collected from 15 older adults through in-depth interviews on older adults' social network experiences during COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 45 publications
(57 reference statements)
1
14
0
Order By: Relevance
“…The older people's desire to participate in social gatherings as found in this current study is essential in old age to eliminate or suppress any feeling of social isolation, loneliness, and other physical and mental health problems (Bruggencate et al, 2019). This finding also corroborates the findings of some studies that revealed that older persons could feel lonely and isolated because of poor social networks (Asante et al, 2021). However, social connectedness among older persons could be improved if the periodic organisation of family gatherings and other community‐based social functions, such as parties, public forums or get‐together ceremonies are encouraged and promoted in society.…”
Section: Discussionsupporting
confidence: 91%
“…The older people's desire to participate in social gatherings as found in this current study is essential in old age to eliminate or suppress any feeling of social isolation, loneliness, and other physical and mental health problems (Bruggencate et al, 2019). This finding also corroborates the findings of some studies that revealed that older persons could feel lonely and isolated because of poor social networks (Asante et al, 2021). However, social connectedness among older persons could be improved if the periodic organisation of family gatherings and other community‐based social functions, such as parties, public forums or get‐together ceremonies are encouraged and promoted in society.…”
Section: Discussionsupporting
confidence: 91%
“…Ten articles published between 2020 and 2022 were included in this review, and all articles focus on SI/L among older adults in the COVID-19 era. Six articles were published in Dovie ( 35 ), Jemal et al ( 36 ), Morgan et al ( 37 ), Ekoh et al ( 22 ), Asante et al ( 26 ), Ekoh ( 38 ). Also, three articles were published in Manyaapelo et al ( 29 ), Ekoh et al ( 28 ), Giebel et al ( 14 ), and one was published in Ekoh et al ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, three articles were published in Manyaapelo et al ( 29 ), Ekoh et al ( 28 ), Giebel et al ( 14 ), and one was published in Ekoh et al ( 39 ). Four of the included articles were focused on the social isolation experiences of older adults in Nigeria ( 22 , 28 , 38 , 39 ), three were from Ghana ( 26 , 35 , 37 ), one each from South Africa ( 29 ), Ethiopia ( 36 ), and Uganda ( 14 ). The four Nigerian articles ( 22 , 28 , 38 , 39 ) have the same first author, are results of different small studies conducted in the same communities (Ihe and Umudioka) and two anonymized care homes in Enugu and Anambra States, Nigeria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations